2020
DOI: 10.1002/ejic.202000397
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Role of Bifunctional Cobalt‐Manganese Catalyst Interactions for Higher Alcohol Synthesis

Abstract: Catalyst promoters are often used to tune or improve performance with little understanding as to how they work. Here we present a fundamental evaluation of cobalt‐manganese interactions in Fischer‐Tropsch (FT) catalysis and evaluate a new bifunctional catalyst for CO dissociation and CO insertion mechanisms. FT has gained considerable attention recently due to the potential to convert bio or municipal waste feeds into commercial fuels and chemicals. Products are commonly highly linear paraffins, but here we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 106 publications
4
20
0
Order By: Relevance
“…Catalytic testing was undertaken to investigate the conversion/product selectivity differences between the Co-0Mn and Co-5Mn catalysts , (see Sections S1.1 and S1.2 for further details of the catalyst synthesis and reactor testing methods, respectively). The benefit of the Mn promotor is to enhance the selectivity to high-value alcohols and other oxygen containing products compared to the unpromoted Co-0Mn (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic testing was undertaken to investigate the conversion/product selectivity differences between the Co-0Mn and Co-5Mn catalysts , (see Sections S1.1 and S1.2 for further details of the catalyst synthesis and reactor testing methods, respectively). The benefit of the Mn promotor is to enhance the selectivity to high-value alcohols and other oxygen containing products compared to the unpromoted Co-0Mn (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The present study focuses on the use of Mn as a promoter, specifically industrial catalysts composed of wet impregnation-synthesized 10 wt % Co on TiO 2 with and without 5 wt % Mn promoter. Previous investigations of 10 wt % Co on TiO 2 have demonstrated that the addition of up to 10 wt % Mn as a promoter can modify the FT reaction selectivity toward long-chain oxygenates and liquid petroleum gas (LPG, C 2 –C 4 ), with the addition of 5 wt % Mn identified as having unusually high selectivity toward desirable long-chain alcohols. , The reason for the high selectivity of 10 wt % Co and 5 wt % Mn on TiO 2 compared to that of the unpromoted catalyst is still debated despite the industrial importance of these materials for the FT reaction. Previous extended X-ray adsorption fine structure (EXAFS) analysis of the Co and Mn coordination in the catalysts has suggested a mixed metal oxide spinel (Co x Mn 3– x O 4 ) with a preference toward MnCo 2 O 4 ( i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Two catalysts were prepared and characterized as reported previously. 25 These two catalysts were 10% cobalt on titania with either 0% or 10% Mn added with the cobalt impregnation. Similar samples with other manganese loadings between 0–10% were also prepared and tested.…”
Section: Resultsmentioning
confidence: 99%
“…Even so, suffering from limited solubility, phase separation seems to be inevitable in bimetallic catalysts. For this reason, interfacial Co 0 –CoO x , and Co 0 –Co 2 C were constructed from Co-spinel, where Co δ+ is active for nondissociative CO adsorption. By tailoring MSI, the ratio of Co 0 /Co δ+ in Co 0 –CoO x can be tuned .…”
Section: Progress On Spinel Catalysts For Thermal-driven C1 Conversionmentioning
confidence: 99%